Design and Optimizing Lansoprazole Solubility through Nanocrystallization: A Dual Polymer Approach - T. Balakrishna (Asian Journal of Pharmaceutics (AJP), 2025)
Aims: The objective of the present study is to increase the aqueous solubility and acid stability of lansoprazole, one of the most common proton pump inhibitors because of poor bioavailability due to poor aqueous solubility and acid sensitivity by formulation as nanocrystals through the antisolvent precipitation method. Materials and Methods: The preparation of lansoprazole nanocrystals was performed by means of an antisolvent precipitation method. The drug was dissolved in ethanol, followed by its immediate injection into an aqueous phase with a stabilizer under highspeed homogenization. Two hydrophilic polymers including polyvinylpyrrolidone (PVP) and polyvinyl alcohol (PVA) were evaluated as stabilizers at different drug-to-polymer ratios (1:1, 1:2, and 1:3). The compositions of the produced nanocrystals were analyzed in terms of particle sizes, dissolving properties, as well as the physicochemical properties utilizing various tests like Fourier-transform infrared spectroscopy (FTIR) and also using the process of the differential scanning calorimeter. Results: Of the formulations, the nanocrystals at the ratio 1:3 drug and polymer in the PVP format performed the better. It showed superior physical stability, mastery of agglomeration of particles, and fast drug release within 1 h. FTIR analysis was used to indicate that there were no chemical interactions between the drug and the polymer. Differential scanning calorimetry analysis showed evidence of partial amorphization in favor of successful nanocrystal formation. The formulations using PVP have performed better in uniformity of particle size and the ability to dissolve more easily as compared to PVA-based ones. Conclusion: The research findings conclude that PVP is a better stabilizer than PVA in the preparation of lansoprazole nanocrystals by a process of antisolvent precipitation. Having the best ratio of drug to polymer equal to 1:3 with PVP gives the best outcomes in accordance with stability and enhancement of dissolution that may enhance the oral bioavailability of the drug.